Unravelling Financial Wrongdoing: A Regulatory Perspective on Crimes in the Indonesian Capital Market - Rizaldy Anggriawan; Muh. Endriyo Susila (IJCLS (Indonesian Journal of Criminal Law Studies), 2023)
The perpetration of offenses within the Indonesian capital market poses a multifaceted challenge, intricately tied to the complexities of evidentiary establishment and legal pursuit within judicial contexts. This research investigates the pivotal role of Indonesia's capital market in its economic development, analyzing the impact of regulatory evolution from BAPEPAM to OJK. It aims to assess the efficacy of stringent regulatory frameworks in maintaining market integrity and bolstering investor confidence, while ensuring legal consequences for transgressors. Employing normative research methods, the study meticulously analyzes statutory regulations and normative constructs governing the capital market, confirming its critical role in national economic well-being and advancement. The transition from BAPEPAM to OJK underscores the dynamic nature of financial markets and underscores the imperative of preserving investor confidence and market integrity. Indonesia's capital market operates within robust regulatory frameworks designed to uphold transparency in securities trading and safeguard investor interests, with explicit prohibitions against fraud, market manipulation, insider trading, and record tampering. These measures underscore Indonesia's unwavering commitment to fostering trust and integrity within its capital market industry, imposing substantive legal consequences on offenders.